Economia Colaborativa - Carvalho, Maria Miguel; Escola de Direito da Universidade do Minho/JusGov (2023)
The importance of analysing the main legal challenges posed by the Sharing Economy - due to the implications of the paradigm shifts in business models and the subjects involved - is indisputable, corresponding to the need to promote the legal security of these practices, which are a driver of economic growth and social well-being. The Centre for Research in Justice and Governance (JusGov) proposed to develop a project in this area in order to identify the legal problems that the collaborative economy raises and assess whether there are already solutions to them, reflecting on the convenience of introducing changes or whether it is necessary to create new regulations. To this end, a multidisciplinary team was formed, which, in addition to lawyers, includes researchers from other areas such as economics and management, from the various groups of JusGov - although with special participation of researchers from the E-TEC (State, Business and Technology) group - and other prestigious national and international institutions. The results of this research are presented in this work, deliberately written in Portuguese, which seeks to affirm Portuguese as a language of science and to maximize the dissemination of the results of this research in the Portuguese-speaking world.The book is divided into three parts: a first introductory part, regarding the emergence and concept of collaborative economy; a second part, with some examples of sharing economy; and, a third part, about the legal regulation of collaborative economy in its various aspects.